Growth Mindset: The Effectiveness of Growth Mindset Training for Karang Taruna - Adelia, Rizka Salma (ANFUSINA: Journal of Psychology, 2025)
This study examines the impact of growth mindset training on Karang Taruna Taruna Bhakti members in Dusun Banyunganti Lor. The training aimed to enhance participants' understanding of growth mindset principles, distinguish between growth and fixed mindsets, recognize the benefits of a growth mindset in an organization, and develop strategies to nurture a growth mindset. A pretest-posttest design was employed, and results showed significant improvements across all key indicators, demonstrating the effectiveness of the training. Participants exhibited high engagement, which contributed to the positive outcomes. However, the study faced limitations, including potential bias from non-standardized surveys and individual differences in responses. These limitations suggest that while the training was effective, the observed improvements may not be uniformly applicable to all members. To address these issues, future training sessions should incorporate standardized survey instruments to reduce bias and consider individual differences. Additionally, logistical challenges, such as the co-trainer shortage and limited access to multimedia tools, should be addressed to enhance the learning experience. Future research could explore the long-term effects of growth mindset training on organizational performance and the impact of integrating interactive, technology-driven methods. Despite the challenges, the training fostered a growth mindset, equipping members with the resilience and adaptability needed for their roles, thereby contributing positively to the community. Keywords: Growth mindset, psychological training, youth organization, organizational development, participant engagement, interactive learning approach